Early germination ability evaluation as a new and rapid method to assess the quality of oilseed rape (Brassica napus L.) seed lots - A.J. Yanegh; M. Khajeh-hosseini; M. Kafi (علوم و فناوری بذر ایران)
In order to evaluate of seed lots germination in early stages of germination test beginning as a rapid method to evaluate the seed vigour, seed samples from twenty seed lots of oilseed rape, from four varieties (Okapy, Hyola 401, Opera and Licord) produced in 1386 to 1390 was provided. Standard germination test carried out in Seed Research Laboratory and soil emergence of seed lots examined in the Research Greenhouse of the Ferdowsi University of Mashhad, Iran. The results showed that the percentages of final germination and normal seedlings and mean germination time had a high correlation (r = 0.84, 0.89 and 0.82, respectively) with the soil emergence of the lots. Germinated percentages in the early days of the test had significant correlation with characteristics of germination and soil emergence of the seedlots. So that, the percentages of germinated seeds on days two and three, correlated with mean germination time (r= 0.97 and 0.92) and with normal seedlings (r = 0.88 and 0.81) and with soil emergence (r = 0.83 and 0.83) respectively. Therefore, the percentages of germinated seeds in the early stages of germination can be used as an alternative and rapid method to assess the final germination, normal seedlings, mean germination time hence seed vigour of oilseed rape.